2019
DOI: 10.1371/journal.pone.0216964
|View full text |Cite
|
Sign up to set email alerts
|

Needing a drink: Rainfall and temperature drive the use of free water by a threatened arboreal folivore

Abstract: Arboreal folivores are particularly vulnerable to the impacts of extreme climate change-driven heatwaves and droughts as they rely on leaf moisture to maintain hydration. During these increasingly frequent and intense weather events, leaf water content may not be enough to meet their moisture requirements, potentially leading to large-scale mortality due to dehydration. Water supplementation could be critical for the conservation of these animals. We tested artificial water stations for a threatened arboreal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 60 publications
(75 reference statements)
1
17
0
Order By: Relevance
“…process these compounds decreases with increasing T a (Beale et al, 2018;Moore et al, 2015). Given that 55% of a ringtail possum's water intake comes from leaves (Munks, 1991), these toxins are likely to constrain rehydration and survival with projected global warming in general, and during heatwaves in particular (Mella et al, 2019;Moore et al, 2015). Possums can avoid consuming leaves at high T a , but reduced foraging will lead to decreased body condition and dehydration (Conradie et al, 2019;Mella et al, 2019), and may impact the growth of young (Cunningham et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…process these compounds decreases with increasing T a (Beale et al, 2018;Moore et al, 2015). Given that 55% of a ringtail possum's water intake comes from leaves (Munks, 1991), these toxins are likely to constrain rehydration and survival with projected global warming in general, and during heatwaves in particular (Mella et al, 2019;Moore et al, 2015). Possums can avoid consuming leaves at high T a , but reduced foraging will lead to decreased body condition and dehydration (Conradie et al, 2019;Mella et al, 2019), and may impact the growth of young (Cunningham et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Given that 55% of a ringtail possum's water intake comes from leaves (Munks, 1991), these toxins are likely to constrain rehydration and survival with projected global warming in general, and during heatwaves in particular (Mella et al, 2019;Moore et al, 2015). Possums can avoid consuming leaves at high T a , but reduced foraging will lead to decreased body condition and dehydration (Conradie et al, 2019;Mella et al, 2019), and may impact the growth of young (Cunningham et al, 2013). Provision of free water to offset reduced intake of leaf water has been trialled for the arboreal and folivorous koala Phascolarctos cinereus, which increased use of supplemented water at high T a (Mella et al, 2019), but such strategies are still impractical beyond a local scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Koalas receive most of their moisture intake from their diet (Munks, Corkrey & Foley, 1996). But they may drink from pools of water during increased periods of drought, and drink more from water stations with higher ambient temperatures and the more days since it last rained (Mella et al ., 2019). Previous research found that captive koalas selected leaves that contained at least 55% leaf moisture (Hume & Esson, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding and water areas, easily arranged along the natural transects [259], can supply many different species [260]. Particularly, water should also be supplemented on the way to the rescue centre.…”
Section: Overview Of Wild Animal Management Challengesmentioning
confidence: 99%